2016
DOI: 10.1175/bams-d-15-00144.1
|View full text |Cite
|
Sign up to set email alerts
|

“Big Data Assimilation” Revolutionizing Severe Weather Prediction

Abstract: Sudden local severe weather is a threat, and we explore what the highest-end supercomputing and sensing technologies can do to address this challenge. Here we show that using the Japanese flagship “K” supercomputer, we can synergistically integrate “big simulations” of 100 parallel simulations of a convective weather system at 100-m grid spacing and “big data” from the next-generation phased array weather radar that produces a high-resolution 3-dimensional rain distribution every 30 s—two orders of magnitude m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 11 publications
3
59
0
Order By: Relevance
“…In addition, the 100-m-mesh forecasts also showed improvements in surface precipitation compared to the 1-km-mesh forecasts. It indicated that rapid-update, high-resolution DA cycles contributed to create a preferable initial condition.Simulating an isolated convective system is one of the challenging issues in the contemporary NWP, and this study suggests that the BDA system be a promising approach to sudden local severe weather prediction, following Miyoshi et al (2016aMiyoshi et al ( , 2016b. This study shows more details of the second case shown by Miyoshi et al (2016b).…”
mentioning
confidence: 72%
See 3 more Smart Citations
“…In addition, the 100-m-mesh forecasts also showed improvements in surface precipitation compared to the 1-km-mesh forecasts. It indicated that rapid-update, high-resolution DA cycles contributed to create a preferable initial condition.Simulating an isolated convective system is one of the challenging issues in the contemporary NWP, and this study suggests that the BDA system be a promising approach to sudden local severe weather prediction, following Miyoshi et al (2016aMiyoshi et al ( , 2016b. This study shows more details of the second case shown by Miyoshi et al (2016b).…”
mentioning
confidence: 72%
“…Recently, Miyoshi et al (2016aMiyoshi et al ( , 2016b reported an innovation of the "Big Data Assimilation" (BDA) technology, implementing a 30-second-update, 100-m-mesh local ensemble transform Kalman filter (LETKF; Hunt et al 2007) to assimilate data from a Phased Array Weather Radar (PAWR) at Osaka University (Ushio et al 2014) into regional NWP models known as the Japan Meteorological Agency non-hydrostatic model (JMA-NHM, Saito et al 2006Saito et al , 2007 and the Scalable Computing for Advanced Library and Environment-Regional Model (SCALE-RM, Nishizawa et al 2015). The PAWR captures the rapid development of convective activities every 30 seconds at approximately 100-m resolution.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most previous studies (e.g., Seko et al, 2004;Wattrelot et al, 2014), except Zeng et al (2016), consider only vertical beam broadening, because numerical models have horizontal grid spacings of several kilometres, whereas they have vertical grid spacings in the lower troposphere of less than one kilometre. However, data assimilation 20 systems must have sub-kilometre horizontal grid spacings as well (e.g., Kawabata et al 2014a, Miyoshi et al, 2016 so that the space interpolators can take account of horizontal beam broadening. In addition, several phased array radars recently deployed in Japan have different beam widths in the vertical and horizontal directions.…”
Section: Space Interpolatormentioning
confidence: 99%